The impact pf parental income and education on the schooling of their children - Arnaud Chevalier; Colm Harmon; Vincent O'Sullivan; Ian Walker (Institute for Fiscal Studies (IFS), 2005)
This paper addresses the intergeneration transmission of education and investigates the extent to which early school leaving (at age 16) may be due to variations in permanent income, parental education levels, and shocks to income at this age. Least squares estimation reveals conventional results - stronger effects of maternal education than paternal, and stronger effects on sons than daughters. We find that the education effects remain significant even when household income is included. Moreover, decomposing the income when the child is 16 between a permanent component and shocks to income at age 16 only the latter is significant. It would appear that education is an important input even when we control for permanent income but that credit constraints at age 16 are also influential. However, when we use instrumental variable methods to simultaneously account for the endogeneity of parental education and paternal income, we find that the strong effects of parental education become insignificant and permanent income matters much more, while the effects of shocks to household income at 16 remain important. A similar pattern of results are reflected in the main measure of scholastic achievement at age 16. These findings have important implications for the design of policies aimed at encouraging pupils to remain in school longer.
Keywords: I20; J62; 330; Early school leaving; intergenerational transmission; Haushaltseinkommen; Bildungsniveau; Kinder; Abbrecher; Großbritannien; Eltern; Bildungsabschluss